The time development of freestyle competitions (100 and 400m races) throughout the history of the modern Olympic Games from Athens 1896 to Rio 2016. - Hazhazi, Kamel; Kadri, Abdelhafid; Hamida, Souraya (sports creativity, 2025)
The paper is a study of the time evolution of the 100 m and 400 m freestyle Swimming competitions through the history of the modern Olympic Games (from the 1896 Athens to the Rio 2016). In addition, it highlights the most important stages that defined the rate of improvement and development and the most important reasons for contributing to that. Besides, it presents the most crowning countries in the competition's history. We used the historical method, based on the records of the International Olympic Committee (CIO). We analyzed the numbers recorded by an intentional sample of 158 male Olympic swimmers. Furthermore, we found that the time of 100 m and 400 m freestyle swimmers have improved continuously, according to the results graph. We divided this into three stages (Athens 1896 to Paris 1924, from Amsterdam 1928 to Munich 1972, and after Munich 1972). We also concluded that the most crowned nation teams in the two competitions are the United States of America (22 medals) and Australia (17 medals)